Discourse Deixis in the American Political Speeches - هدى هادي خليل (College of Education for Women, 2019)
The feature that prevails in spoken political discourse - especially with regards to the fact that it is otherwise used in the written one - is relatively high degree of formality. It is then just logical that formality is usually accompanied with more polite forms and higher degree of impersonality. Such discourse is characterized by the choice of specific vocabulary and syntactic structures as well. However, there are some tendencies to bring political speech nearer to the everyday discourse and that is why political speeches have been becoming more informal and personal. Like any other types of discourse, the American political speeches are loaded with deictic expressions that form an essential complementary part of any text. The present paper aims at presenting a full presentation of the concept of deixis in general and the discourse deixis in particular. This presentation is the subject matter of the first and second sections of the paper. In the third section discrimination is drawn between two overlapping concepts: discourse deixis and anaphora. The main aim of the present paper is to investigate the discourse deixis in the American political speeches, as a type of institutional talk, to find out the way this linguistic phenomenon used in the American political speeches and to see whether there is a special strategy for the use of the discourse deixis in this type of text. To achieve this aim, three American political speeches have be downloaded randomly from the internet from the website ofhttp://www.americanrhetoric.com/speeches/wariniraq,and analyzed carefully. Each speech is delivered by a different politician; the first is for Barak Obama, the second is for Condoleezza Rice, and the third is for Paul Bremer. The analysis of the discourse deixis represents the practical part of the paper which is introduced in section four. The practical part also includes a number of conclusions which the analysis has come with.